Constructing Identity: Insights from Second Language Teachers' Biographies - Castro Mosqueda, Héctor (Colombian Applied Linguistics Journal, 2025)
This study explores the intricate and evolving nature of language teacher identity (LTI) through a narrative inquiry into the life stories of four Mexican English language teachers. LTI plays a pivotal role in shaping educators' self-perceptions, pedagogical decisions, and classroom interactions. Using a qualitative narrative approach, the research delves into the participants' biographies to reveal how their personal experiences, cultural backgrounds, and professional contexts influence the formation of their identities. The findings highlight three central identity frames: instructional, disciplinary, and professional. Instructional identities are molded by classroom practices and student interactions, while disciplinary identities are shaped by the teachers' knowledge and beliefs about language education. Professional identities, on the other hand, emerge from a blend of experiences, motivations, and aspirations. Notably, the study uncovers the significant role of caring practices in resolving identity tensions, aligning with ethics of care theory. These insights enhance the understanding of LTI as a dynamic and continually negotiated construct, influenced by various educational contexts. The study underscores the importance of reflective and caring practices in teacher education programs to support the comprehensive development of teacher identity.